Exile, Immigration and Piety: The Jewish Pietists of Medieval Germany, from the Rhineland to the Danube - Shoham-Shṭainer, Efrayim (Jewish studies quarterly, 2017)
This article re-considers the migration of the Kalonymide family of pietists from medieval Speyer to Regensburg, suggesting a revised date for the move and an expanded interpretation of the reasons for it. Drawing on both halakhic and hagiographic sources, it demonstrates a more inclusive methodology for attempting to reconstruct historical events from incomplete and even apparently conflicting sources. It attempts to show that the prominent rabbi who moved to Regensburg in the 12th century was not Rabbi Yehudah the Pious, but his father Rabbi Shmuel, and two accounts of the migration that seem unrelated different may share a historical kernel associated with the pietistic agenda that was interpreted in radically divergent ways.